Impact of iPod Touch-Supported Repeated Reading on the English Oral Reading Fluency of L2 students with Specific Learning Difficulties - Papadima-Sophocleous, Salomi (My University, 2014)
In recent years the use of new technologies has been extensively explored in different aspects of language learning pedagogy. The objective of this research was to investigate the impact Repeated Reading activity, supported by iPod Touch could have on the English Oral Reading Fluency (ORF) of second language university students with Special Learning Difficulties (SpLD) at Cyprus University of Technology. As part of their university courses, students have two compulsory English courses. Due to their SpLD and low level of language competence, the eight participants enrolled in the English programme for students with SpLD. This programme is based on the phonological approach and the research done in methods dealing with dyslexia (Shaywitz et al., 2004). After being introduced to the iPod-supported Repeated Reading activity, students worked independently for 8 weeks. They listened and replicated three recorded texts performed by native speakers, using Voice Memo. Texts were based on specific phonetic rules the students had to master. Students recorded their best performance of each text reading, using DropVox. Curriculum-Based Measurement, adapted by Rasinski (2004), was used to measure students’ automaticity (speed and accuracy), and an adapted version of Zutell and Rasinksi’s (1991) Multidimensional Framework to measure prosodic features of fluency. A phonemic accuracy scale was developed and used to assess students’ performance related to specific phonemes students had difficulty with. Data analysis revealed that the independent out-of-class use of Repeated Reading, supported by iPod Touch technology helped in increasing students’ automaticity, improving their prosodic features of fluency, including that of specific phonemes.
Keywords: Oral Reading Fluency (ORF); Special Learning Difficulties (SpLD); Dyslexia; Reading deficiencies; Phonics; Repeated reading; iPod Touch Technologies